Theory and craft of the scenographic model - Payne, Darwin Reid, 1931-2016 (Southern Illinois University Press, 1985)
Through diagrams, sketches, and models, along with explications of the essential tools and materials required, Payne defines and delineates the precise step-by-step procedures of scenographic modelmaking: the basic preparations of construction, the process of making the model, and the experimental aspects of modelmaking. This new edition with 50 additional illustrations and other new information offers teachers, students, and beginning professionals alike a complete and comprehensive approach to creating and constructing the scenographic model.